Utilization of Sawdust Waste as Organic Fertilizer for Vegetable Farming in Tunggulo Village - Silviana Arsyad; Zulzain Ilahude; Yunnita Rahim (Universitas Muhammadiyah Sidenreng Rappang, 2025)
Sawdust waste is a by-product of various wood industry activities in Gorontalo. The problem of sawdust waste often causes rotting which produces methane gas and is one of the greenhouse gases that causes global warming. Tunggulo Village has the potential as a food barn, horticulture, and secondary crops, and has rice production that is recognized as having good quality. This activity aims to socialize the importance of processing sawdust waste into organic fertilizer and its benefits for the environment and applying it to vegetable plants. The implementation method with several stages, namely socialization activities, implementation of technical training and assistance, application of sawdust fertilizer utilization on plants, monitoring and evaluation. The results of this community service began with an initial survey which showed that several respondents still viewed sawdust as useless waste. This reflects that public perception of the potential for productive use of sawdust is still low. Training and technical guidance in Tunggulo Village may not have any local examples or practices regarding the use of sawdust as organic fertilizer. Training activities begin with an introduction to the process of processing sawdust into organic fertilizer, which is then directed to utilize agricultural waste as an effort to maintain and improve the quality of agricultural land